2017
DOI: 10.3390/s17092099
|View full text |Cite
|
Sign up to set email alerts
|

Chlordetect: Commercial Calcium Aluminate Based Conductimetric Sensor for Chloride Presence Detection

Abstract: Chloride presence affects different environments (soil, water, concrete) decreasing their qualities. In order to assess chloride concentration this paper proposes a novel sensor for detecting and measuring it. This sensor is based on electric changes of commercial monocalcium aluminate (CA) when it interacts with chloride aqueous solutions. CA is used as a dielectric material between two coplanar capacitors. The geometry proposed for this sensor allows to assess the chloride content profile, or to make four ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For the sensors that track the conductivity of cementitious material to monitor Cl − content 43,49 and humidity, 9,45 the non-homogeneous penetration of Cl − ions and the intrusion of other species like sulfate ions may change their dielectric properties and cause an unstable shift in the measurement. Furthermore, for the steel fiber reinforced concrete, the measurement of electrical resistivity is disturbed by the presence of steel fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the sensors that track the conductivity of cementitious material to monitor Cl − content 43,49 and humidity, 9,45 the non-homogeneous penetration of Cl − ions and the intrusion of other species like sulfate ions may change their dielectric properties and cause an unstable shift in the measurement. Furthermore, for the steel fiber reinforced concrete, the measurement of electrical resistivity is disturbed by the presence of steel fibers.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Another Cl − sensor made of two copper capacitors and a dielectric layer of calcium aluminate (CA) in its middle is designed as the electric capacitance of CA is proportional to Cl − concentration. 43 For the pH measurement with Ir/IrO 2 electrode, a potential-pH response in the pH range of 9–13.5 was obtained. 8,44 McCarter et al have reported an embeddable electrical conductivity sensor which consists of 10 stainless-steel electrode pairs mounted on a small Plexiglass, along with four thermistors.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…The XRD diffractogram of GPA2 was also elevated from 15°to 32°, which showed that there was introduction of the amorphous structure into the geopolymer. The GPA2 geopolymer also contained Calcium Aluminate Silicate Hydrate (CASH) in addition to CSH [30]. The additional CASH was a result of the increase in the aluminate available in the activator which also led to an increase in the strength of GPA2 in comparison to GPS1 and GP0 (Fig.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…Although the destructive characterization of chloride content is now fully applied all over the world, it is widely recognized that the procedure is cumbersome and requires a lot of time, and that any non-destructive technique able to provide this information would bring an appreciable improvement to the assessment methodologies [4]. The complexity of the diagnosis is partially due to the multiple influences included during the measurement and the inversion process, all of which act as sources of uncertainty in the diagnosis.…”
mentioning
confidence: 99%